Experimental study of heat recovery for heat pipe in liquid desiccant dehumidification system - Nguyen, Phuoc Minh Tam (2015)
This thesis studies the heat transfer performance of the heat pipe and the effect of heat pipe on regeneration performance in the Liquid Desiccant Dehumidification System (LDDS). Based on experimental approach, the project mainly consists of three sections which are the studies of the heat transfer of heat pipe, experiment analysis and conclusion. The studies of the heat transfer of heat pipe includes the heat conduction, the heat transfer of finned tube, the heat transfer coefficient, the pressure drop of fluid and eventually, the design procedure of heat pipe exchanger. Based on the expected temperature of the recovered air, the heat exchange area of the heat pipe exchanger can be calculated using mathematical formula. Consequently, the calculated heat exchange area would be a reference to choose how many heat pipes are used. For the heat pipe exchanger itself, some experiments were conducted to research the effect on the heat exchange rate and the heat exchange efficiency under the condition of changing one of three variables which are the air flow rate, the inlet hot air temperature and the row number of heat pipe respectively. In LDDS, some experiments were completed to compare the regeneration performance with or without heat pipe exchanger. Using the heat pipe exchanger in the regeneration unit of LDDS can recover some thermal energy loss, thereby, enhance the regeneration performance. The objective of this project is to investigate the heat transfer of the heat pipe exchanger in theory, and the heat transfer performance and the effect on the regeneration performance in LDDS by analyzing the experimental data.